Prioritizing gender equity and intersectionality in Canadian global health institutions and partnerships - Bianca Carducci; Emily C. Keats; Michelle Amri; Katrina M. Plamondon; Jeannie Shoveller; Onome Ako; F. Gigi Osler; Carol Henry; Nitika Pant Pai; Erica Di Ruggiero (Public Library of Science (PLoS), 2022)
Despite governmental efforts to close the gender gap and global calls including Sustainable Development Goal 5 to promote gender equality, the sobering reality is that gender inequities continue to persist in Canadian global health institutions. Moreover, from health to the economy, security to social protection, COVID-19 has exposed and heightened pre-existing inequities, with women, especially marginalized women, being disproportionately impacted. Women, particularly women who face bias along multiple identity dimensions, continue to be at risk of being excluded or delegitimized as participants in the global health workforce and continue to face barriers in career advancement to leadership, management and governance positions in Canada. These inequities have downstream effects on the policies and programmes, including global health efforts intended to support equitable partnerships with colleagues in low- and middle- income countries. We review current institutional gender inequities in Canadian global health research, policy and practice and by extension, our global partnerships. Informed by this review, we offer four priority actions for institutional leaders and managers to gender-transform Canadian global health institutions to accompany both the immediate response and longer-term recovery efforts of COVID-19. In particular, we call for the need for tracking indicators of gender parity within and across our institutions and in global health research (e.g., representation and participation, pay, promotions, training opportunities, unpaid care work), accountability and progressive action.